2021
DOI: 10.3233/bmr-200152
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of response in radial Extracorporeal Shock-waves Therapy for Myofascial and Articular Pain: A retrospective cohort study

Abstract: BACKGROUND: Myofascial Pain Syndrome causes disability in daily life activities and despite all efforts, it continues to be a challenge, perpetuating suffering, overloading services and costs. New treatment options need to be tested. OBJECTIVE: We aimed to quantify the rESWT short-term analgesic effect and identify the success predictors through results comparisons achieved in MPS and Articular Pain (AP). METHOD: Retrospective cohort study of 1,580 patients with Myofascial Pain Syndrome or Articular Pain under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Although myofascial pain can involve a wide range of pain points up and down the body; neck, shoulder, and back pain is the most common in clinical practice, and the degree of pain is the most significant (3). A study (4) has shown that sedentary, excessive mental stress and long-term…”
Section: Introductionmentioning
confidence: 99%
“…Although myofascial pain can involve a wide range of pain points up and down the body; neck, shoulder, and back pain is the most common in clinical practice, and the degree of pain is the most significant (3). A study (4) has shown that sedentary, excessive mental stress and long-term…”
Section: Introductionmentioning
confidence: 99%